Pengaruh Prilaku Konsumen Online Shop Terhadap Konveksi Di Daerah Soreang - Ibda Nisaul Wahdah; Ageng Saepudin Kanda S (Jurnal Riset dan Inovasi Manajemen, 2024)
The influence of several consumer behaviors that prefer to carry out online shopping transactions is the main study from the results of interviews from several convection industry businesses conducted in the Soreang area to find out what consumers are more interested in regarding their attitudes and shopping methods and what they are more interested in when making purchases. In the current era, the progress of the times and the development of technology influence consumer behavior to fulfill their needs so that it is more comfortable and easier to do, and find out several responses from the results of interview surveys at 25 convections in the afternoon area, what influences the production of goods produced and income for convection itself